1989
DOI: 10.1161/01.hyp.13.5.480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perfusion pressure on energy and work of isolated rat hearts.

Abstract: A chemomechanical study of hypertrophied hearts of 6-month-old spontaneously hypertensive rats (SHR) and that of age-matched Wistar-Kyoto (WKY) rats was carried out, analyzing the response of the heart to steady-state changes in coronary perfusion pressure. The ratio of heart (dry)-to-body (wet) weight of WKY rats was 0.37±0.02 (10 3 ) and for SHR was 0.58±0.03 (1(T 3 ) (/7<0.01). In the apex-ejecting, isolated, pyruvate-perfused working hearts of WKY rats and SHR, coronary flow was constant when coronary perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Although the contractility of the SHR heart is often overcompensated (14,24,39,53,61) and the energy utilization can be more efficient in LVH (45,61), why SHR hearts examined in the current study show higher baseline energy level is not clear. In fact, literature reports are mixed on the basal HEP level in moderate LVH: decreased, normal, or slightly increased (6,41,53,57,61).…”
Section: Hypertrophic Model and Its Baseline Physiology/metabolismmentioning
confidence: 82%
See 4 more Smart Citations
“…Although the contractility of the SHR heart is often overcompensated (14,24,39,53,61) and the energy utilization can be more efficient in LVH (45,61), why SHR hearts examined in the current study show higher baseline energy level is not clear. In fact, literature reports are mixed on the basal HEP level in moderate LVH: decreased, normal, or slightly increased (6,41,53,57,61).…”
Section: Hypertrophic Model and Its Baseline Physiology/metabolismmentioning
confidence: 82%
“…Yet many studies have also demonstrated an altered energy metabolism in LVH and have suggested a cellular hypoxia (15,41,61,64). Consistent with possible O 2 limitation, a depressed O 2 consumption in the hypertrophic myocardium, especially under low perfusion pressure, has been reported (9,61).…”
mentioning
confidence: 88%
See 3 more Smart Citations